Training and Auditing Material Effectiveness for Good Manufacturing Practices and Critical Control Points of Drinking Water Production Plants in Cambodia - Kong, Leab; Wimonpeerapattana, Wanphen; Chavasit, Visith; Photi, Juntima (Thai Journal of Science and Technology, 2019)
Abstract The major public health problem in Cambodia is inaccessibility of safe drinking water; people therefore must rely on bottled drinking water, especially the 20-liter pack size. Consequently, Cambodian officers must increase their knowledge on production processes and hazard control. In this study, the training and auditing materials were prepared based on the Codex Alimentarius guideline and related researches. The materials were then translated into Cambodian, and evaluated for its effectiveness in order to be used for monitoring the quality and safety of Cambodian drinking water. A two-day lecture was conducted, attended by about 50 participants who were pre-tested for their basic knowledge. For each part of the lecture, a post-test was conducted. After the lecture session was completed, 16 plants were audited by an expert and the trainees. Effectiveness of the training material was evaluated based on performance in the post-test and auditing. Results revealed that post-test scores were significantly higher (p < 0.05) than those of the pre-test for all parts. Scores from 39 out of 73 audits of the trainees were not significantly different from those of the expert. The auditing performance was significantly correlated with post-test score, trainee affiliation, location of the affiliation, and the GMP status of the plant (p < 0.05). Information on the post-test score and auditing performance indicated that the passing score for the post-test should be 60 %. The training and auditing materials were thus effective in improving trainee knowledge, which should capable them on monitoring quality and safety of drinking water in future. Keywords: Cambodia; drinking water; safety; training; auditing